An average weight whole-process method for predicting mechanical and ductile fracture performances of HSS Q690 after a fire. (10th December 2018) - Kang, Lan; Ge, Hanbin; Suzuki, Motoya; Wu, Bo
Highlights: An average weight whole-process method is proposed across various structural steels. The effect of temperature on ductile fracture property is not reflected by the toughness parameter. The analytical results using the proposed method agree well with test results by an average parameter. The predictive equations of ductile fracture parameters are proposed. Abstract: An average weight whole-process method is proposed to evaluate the force-displacement curve, ultimate capacity, ductile fracture displacement and fracture force of high strength steel (HSS) Q690. Finite element analyses of 26 specimens are carried out to demonstrate the accuracy and application of the average weight whole-process method to predict the mechanical and ductile fracture performance of the HSS Q690. Modeling concepts and procedures for characterizing the material parameters of the average weight whole-process method are described using tensile tests conducted on the specimens after cooling down from various temperatures ranging from 20 °C to 900 °C as presented in a previous paper. In this method, four important parameters (including the equivalent plastic strain at the neck, true stress at the neck, weight parameter and toughness parameter) can be obtained through combining test result and finite element analysis. Finite element analytical results reveal that the effect of temperature experienced on the ductile fracture performance of the HSS Q690 is reflected by the equivalent plastic strain at the neck, the true stress at the neck and the weight parameter, and not by the toughness parameter. It is concluded that the proposed method in this study can predict the post-fire force-displacement curve, ultimate bearing capacity and ductile fracture performance with good accuracy across various temperatures experienced. Finally, the predictive equations of ductile fracture parameters based on all of the test and simulated results in this study are proposed.